2015
DOI: 10.1371/journal.pone.0128360
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of EGFR and ErbB-3 Heterodimerization to the EGFR Mutation-Induced Gefitinib- and Erlotinib-Resistance in Non-Small-Cell Lung Carcinoma Treatments

Abstract: EGFR mutation-induced drug resistance has become a major threat to the treatment of non-small-cell lung carcinoma. Essentially, the resistance mechanism involves modifications of the intracellular signaling pathways. In our work, we separately investigated the EGFR and ErbB-3 heterodimerization, regarded as the origin of intracellular signaling pathways. On one hand, we combined the molecular interaction in EGFR heterodimerization with that between the EGFR tyrosine kinase and its inhibitor. For 168 clinical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 73 publications
(150 reference statements)
0
22
0
3
Order By: Relevance
“…However, novel inhibitors of EGFR are suspected to suffer from similar anticancer drug resistances than the established inhibitors. Beside so far unknown mutations which may affect the inhibitor binding to EGFR, another mechanism of drug resistance may lower the inhibitor activity: a receptor heterodimerization 12 . Normally, the ligand-activated EGFR undergoes a receptor dimerisation with a neighboured EGFR receptor 13 .…”
Section: Introductionmentioning
confidence: 99%
“…However, novel inhibitors of EGFR are suspected to suffer from similar anticancer drug resistances than the established inhibitors. Beside so far unknown mutations which may affect the inhibitor binding to EGFR, another mechanism of drug resistance may lower the inhibitor activity: a receptor heterodimerization 12 . Normally, the ligand-activated EGFR undergoes a receptor dimerisation with a neighboured EGFR receptor 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The human epidermal growth factor receptor (EGFR) belongs to the ErbB family of receptor tyrosine kinases (RTKs) and plays an important role in the pathogenesis and progression of different cancers, thus it has become a major subject for scholars ( 27 , 28 ). In the study by Wang et al ( 29 ), EGFR mutation-induced drug resistance has become a major threat to the treatment of NSCLC; the resistance mechanism involves the modification of intracellular signaling pathways. According to Xu et al ( 30 ), molecular genetic analysis showed that KRAS mutations were frequent in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that cause exchanges of such amino acids led to resistance developments against established inhibitors 22 . Another recently discovered resistance mechanism of cancer cells is a possible heterodimerization of the EGFR receptor with IGF-1R as another activated tyrosine kinase 23 , 24 . Such described heterodimerizations made void the EGFR-specific inhibitory activity of an established EGFR inhibitor.…”
Section: Methodsmentioning
confidence: 99%